Plastic-derived carbon dots for sustainable environmental applications - Liang, Lili (Nanyang Technological University, 2024)
Carbon dots (CDs) are a type of carbon nanomaterials (CNMs) with unique properties, including ultrasmall size, excellent water dispersibility, tunable photoluminescence, easy surface funcionalization, low toxicity, and biocompatibility. Owing to their attractive characteristics, CDs have drawn significant interest across diverse application fields. Nowadays, the massive production, consumption, and random disposal of plastics result in accumulation of tremendous non-biodegradable plastic wastes in landfills and natural ecosystems, which could potentially induce environmental pollution and impose threat to human health and ecosystem. The carbon-rich nature of plastic wastes makes them become appealing carbonaceous feedstocks for the fabrication of CDs at low production cost. However, studies focused on this field are still in the preliminary stage, with enormous possibilities remaining to be explored regarding the optimization of synthetic approaches and CD applications in various essential areas. Therefore, this thesis aims at upgrading non-degradable plastic wastes into valuable CDs through eco-friendly and facile synthetic approaches and further investigating their potential applications in the fields of analytical detection and agriculture. Firstly, exhausted RO membrane modules were utilized as feedstocks to produce valuable pyrolysis products and CDs through thermochemical conversion followed by H2O2-assisted hydrothermal method. The synthetic approach of CDs was optimized via adjustments of carbon precursor size, H2O2 concentration, and reaction time. The resultant CDs possess desired properties including excellent water dispersibility, narrow size distribution of 1.3–6.8 nm, high stability, and strong blue fluorescence with a quantum yield of 6.24%. The feasibility of obtained CDs for Fe3+ determination in different water samples is validated and the possible detection mechanism is investigated. Secondly, we successfully achieved the conversion of waste polyethylene terephthalate (PET) bottles into CDs and used them as seed nano-priming agents for green pea seeds. It was found CD priming could efficiently facilitate seed germination and seedling growth of pea plants at all applied concentrations (0.25-2 mg/mL). CD treatment also upregulated multiple biochemical parameters in the plant system favorable for pea development, including root vigor, chlorophyll content, carbohydrate content, and antioxidant enzyme activities. Furthermore, comparative studies of CDs and carbon nanotubes (CNTs) derived from waste plastics were then conducted to investigate their respective effects on pea plant development as nano-priming agents. Different from the previous study which was carried out in a hydroponic system, this study implemented pea cultivation in soil culture treated with or without salt stress (200 mM NaCl). The results demonstrated that both CNMs could promote seed germination and seedling growth and enhance salt tolerance of the plant. A certain degree of surface destruction was observed from the seed coat primed with CDs and CNTs, which could be induced by surface erosion and mechanical interaction, respectively. Besides, it was found that under equivalent concentrations, CDs and CNTs triggered plant response at varying levels and ultimately resulted in variable pea seedling development and salt tolerance. This study provides new insights of implementing CNMs derived from plastic wastes as seed priming agents for agricultural practices, such as saline stress amelioration. Overall, the above studies are expected to offer alternative options for waste management using waste-to-material strategy, thereby contributing to the development of a resilient and reliable circular economy framework.